Climate-Smart Village AR4D Approach: Synthesis of lessons learned - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
CCAFS has developed the Climate-Smart Village (CSV) approach as a means to address the need for proven and effective location-specific CSA options in the context of climate change, seeking to fill knowledge gaps and stimulate their scaling. Evidence is needed on which options generate CSA-related outcomes, where the options should be targeted, the costs involved, their expected co-benefits or trade-offs with other outcomes. Research in CSVs revolve around understanding the relative synergies and trade-offs of different CSA portfolios in terms of productivity, adaptation and mitigation outcomes and their context-dependencies, the gender, social and nutrition dimensions of promising CSA options, and which might be the most successful scaling- up strategies and processes.